Jump Game Development as a Media in Improving Rough Motoric of The Kindergarten Students in Malind District-Merauke (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this research is to develop and produce a learning model for kindergarten students in Malind District in the form of Jump games. This method is a development research that refers to the Borg & Gall which has conducted, namely: (1) Conducting Preliminary Research and Gathering Information, (2) Developing Initial Product Forms, (3) Evaluation, (4) Revise First Product, (5) Field trials (20 students), (6) Revise Final Product and (7) Final Results through field trial revision. The questionnaire is used in collecting the data; the results obtained were expert evaluation, small group trials, and field trials. Data in the form of production results regarding product quality, product improvement, and the results of questionnaires by the students. Descriptive percentage used in analyzing data to reveal the psychomotor, cognitive, and affective aspects of students after using the product. Based on the results of the trials obtained, were 82% of Physical Education Experts (Good) and Field Trial 80% (Good), Learning Experts 83% (Good), and Small Group Trials 81% (Good). Based on the data that has been received above, it can be stated that Jump Game can be used by Kindergarten Students in Malind District, Merauke Regency because it can be accepted by students and produces a learning products.